Five alternative splicing variants of the TYR gene and their different roles in melanogenesis in the Muchuan black-boned chicken. Issue 1 (2nd January 2019) - Yu, S.; Wang, G.; Liao, J.; Tang, M.
ABSTRACT: 1. The TYR gene encodes tyrosinase, a multifunctional enzyme that is essential for melanin biosynthesis in melanocytes. This experiment involved the cloning and characterisation of the TYR gene in chicken. Five alternative splice variants were identiﬁed in the black feather bulb and designated as TYR-AS1, TYR-AS2, TYR-AS3, TYR-AS4 and TYR-AS5. 2. Among the 11 chicken tissues examined, the feather bulb, comb and skin showed higher levels of all TYR variants. All TYR variants were expressed at significantly different levels in black and white feather bulbs ( P < 0.05) and may be involved in melanin formation in plumage. Only TYR-AS1, which plays an important role in muscle melanogenesis, was significantly differentially expressed between black and white muscle ( P < 0.01). All TYR variants were expressed at significantly different levels in black and white skin ( P < 0.01). 3. The mRNA expression levels of the 5 variants were closely associated with skin melanogenesis in the chicken. These findings provide new clues to the molecular mechanism of melanin formation in the Muchuan black-boned chicken.